STUDI KELAYAKAN BISNIS BPRS AR RAHMAN UAD - Muhammad Safar Nasir; Sumaryanto Sumaryanto; Ulinnuha Yudiansa Putra (Universitas Ahmad Dahlan, 2019)
The public's expectation of sharia services is increasing, so the demand for sharia-based financial institutions is needed. One form of sharia financial institutions is the Sharia People's Financing Bank (BPRS). Ar Rahman UAD Islamic bank mini is a sharia banking laboratory managed by the accounting study program of the Faculty of Economics, UAD, which is the forerunner of the establishment of BPRS UAD. Operations carried out in Arrahman UAD's mini Islamic banks are with real (real) transactions such as in Islamic banking. Ar Rahman's market share is predicted to grow with more students. The business feasibility study will describe in more detail the projected development of the mini bank into a BPRS UAD financial institution.The results of the preparation of the study feasibility of BPRS UAD are in terms of legal legal aspects that the BPRS UAD will be in the form of a PT and start from the capital side in class 3 which is IDR 5,000,000,000. The marketing aspect with the marketing mix model is seen from the product strategy, price strategy, location strategy and promotion strategy. Technical aspects / operations related to the banking operational support system in collaboration with BISKOM UAD. Operational management aspects are very supportive with abundant human resources owned by UAD. Supported by many study programs that teach about Islamic banking operations. And SWOT analysis that has been analyzed in detail about strengths, weaknesses, opportunities and threats.